EFFECT OF MAGNETIC PLATE IN MEMORY OF RATS - de Melo Gonçalvex, Neuza Maria Ferraz; Gonçalves, Adriane Granato; Somensi, Lincon Bordignon; Ferraz, Neliza . (Archives of Veterinary Science, 2016)
It is understood as Magnetism, the physical process that occurs between two opposite poles of a magnet and the science of this phenomenon that takes place in being, Magnotherapy. In this context, concerned about the magnetic decrease, the researchers initiated studies on the use of therapies for restoring health to the cellular level and energy replacement that the body needs to rehabilitate itself from aggression from the environment. The objective of this study was to evaluate the effect of the magnetic board in relation to the memory of rats, Wistar (Rattus norvegicus var albinos), for periods of 5, 10, and 20 minutes in a special compartment, called the labyrinth. Justifies the importance of this work, the evaluation of the memory content when using the magnetic board in the process of knowledge is encoded, retained and later recovered, but due to the stress of busy life nowadays, man is decreasing your memory and your energy boost. The methodology refers to the evaluations of the rats in search of food memory after the course of several compartments. The results found on the observation with the 12 rats, the experimental group, in a period of 20 minutes with the magnetic board and the percentage of correct answers with£12 days plate dwell time are significantly different from the percentage of correct answers of mice plate length of stay> 12 days. Therefore, statistically confirmed that the magnetic card was effective in these mice memory in search of food, but there was no statistical difference in the times of observations 5 and 10 minutes in experimental groups.